Legal Protection for Online Loan Customers - Itok Dwi Kurniawan; Ismunarno; Suyatno (UNIVERSITAS PGRI YOGYAKARTA, 2023)
Abstract The era of the industrial revolution 4.0 is marked by convenience in all things through information technology. One of the conveniences experienced by people in this digital era is in the field of Financial Technology. One of the fields in Fintech is online-based cash loans, in online-based lending and borrowing activities cause a problem, namely debtors who experience verbally abusive billing methods and personal data security. The purpose of this study is to provide information regarding how regulations in Indonesia provide legal protection and the role of OJK for online loan customers. The method used in this study uses normative legal research methods, by collecting secondary data that provides an explanation of the primary law used in this study, including books, scientific papers, papers, journal articles, and so on related to this research. . The results of this research are to provide legal protection for online loan debtors by carrying out a technology-based corporate supervision system. The form of protection provided by OJK will require OJK to stop business activities if the violation results in losses. Meanwhile, violations involving data dissemination, illegal access, and intimidation can be followed up through the realm of criminal law and submit a complaint to the Indonesian National Police. Keywords: Legal Protection, Online Loans, Online Loan Customers